Mobile Assisted Language Learning in EFL Contexts: Maximizing Vocabulary Acquisition through Messenger Apps - Chakir, Mohamed; Lamjahdi, Ahlam (International Journal of Language and Literary Studies, 2024)
Mobile Assisted Language Learning (MALL) has drawn the attention of researchers worldwide and is gaining more popularity in various educational backgrounds. In this context, the present study is conducted to investigate the effectiveness of MALL in English as a Foreign Language (EFL) settings. The study comprised 90 Moroccan high school students, aged between 15 and 17 years old, divided equally into experimental (N = 45) and control (N = 45) groups. The two groups underwent two treatments, which lasted for two weeks. During the first week, the first experimental group was provided with two vocabulary items via WhatsApp messenger three times a day for seven consecutive days; however, the control group received a printed list of the 14 items at the beginning of the week. In the second week, the groups switched treatments with another set of 14 words. A pretest was used to measure participants’ vocabulary knowledge of the target items. Additionally, two immediate posttests were administered at the end of each week to measure the subjects’ vocabulary learning during the experiment, while a delayed test was used four weeks after the end of the experiment to assess their vocabulary retention. The pre-and delayed-test results were insignificant since they did not show any difference between the groups, while the immediate post-test scores revealed a significant difference, with the experimental groups outperforming the control groups. In short, this study contributes to the growing body of research on MALL and provides insights for language instructors willing to integrate technology for effective vocabulary learning.